Integrating Forensic Analysis and Sustainable Design for Slope Stabilization: A Case Study Using Waste Tire-Filled Gabion Structure (WTFGS) - Solahuddin Daud; Ishak, Mohd Fakhrurrazi; Qistina Hannah Hussein; Puteri Izrina Ismi; Muhammad Farhan Zolkepli (International Journal of Integrated Engineering, 2025)
This study presents a forensic investigation and geotechnical modelling of a landslide disaster and associated slope failure that adversely affected nearby infrastructure. The investigation involved geological mapping and geotechnical investigation through borehole drilling, followed by laboratory testing to characterise the physical index and engineering properties of the soil. Slope stability analyses were performed using SLOPE/W to show the stability analysis (Factor of Safety - FOS) for both the current failed slope condition and a proposed remediation design that incorporates sustainable materials. The proposed solution utilised a waste tire-filled gabion structure (WTFGS) as a sustainable slope retaining technique. Results indicated that the FOS for the existing slope was 0.979, classifying it as unstable. However, with the implementation design of WTFGS, the FOS improved to 1.580, indicating a stable slope in accordance with standard guidelines. These findings demonstrate that using waste materials to replace conventional materials is a practical remediation technique and a sustainable solution for slope stabilisation in new construction and slope repair applications. The integrated methodology strengthens failure assessment and supports the development of effective, sustainable slope stabilization solutions.